The effects of professional ethics and commitment on audit quality - Aliasghar Nasrabadi; Aliakbar Arbabian (Management Science Letters)
This paper presents a study on the effects of professional ethics and commitments on audit quality. The population of this survey includes all audit managers who were active in auditing official statements of different firms listed in Tehran Stock Exchange in 2014. The study designs a questionnaire in Likert scale and distributes it among 152 randomly selected managers. In our survey, professional ethics consists of four items including confidentiality and impartiality, professional competence, accountability and individual values while organizational commitment consists of three items including emotional commitment, continues commitment and fundamental commitment. Using Pearson correlation as well as regression models, the study has determined a positive and meaningful relationship between professional ethics as well as commitment and audit quality.